2019
DOI: 10.1101/651182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unfolded protein-independent IRE1 activation contributes to multifaceted developmental processes in Arabidopsis

Abstract: As an initial step for the unfolded protein response (UPR) pathway, the luminal domain of inositol requiring enzyme 1 (IRE1) senses unfolded proteins in the endoplasmic reticulum (ER). Recent findings in yeast and metazoans suggest alternative IRE1 activation without the sensor domain, although its mechanism and physiological significance remain to be elucidated. In Arabidopsis, the IRE1A and IRE1B double mutant (ire1a/b) is unable to activate cytoplasmic splicing of bZIP60 mRNA and regulated IRE1-dependent de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…A. thaliana has three IRE1 genes, two full length genes, AtIRE1a and ‐b , discovered by Koizumi et al (2001), and a shorter version called AtIRE1c (Figure 4). Arabidopsis lyrata has four IRE1 genes, AlIRE1a , ‐b , ‐c and c‐like (Mishiba et al, 2019). Surprisingly, there are three ZmIRE1 genes in maize ( Zea mays B73) – two full‐length genes, which cannot be classified as either IRE1a or ‐b ‐like and a shorter one, which by virtue of its size suggests that it is IRE1c ‐like.…”
Section: Are Two Ire1s Better Than One?mentioning
confidence: 99%
See 3 more Smart Citations
“…A. thaliana has three IRE1 genes, two full length genes, AtIRE1a and ‐b , discovered by Koizumi et al (2001), and a shorter version called AtIRE1c (Figure 4). Arabidopsis lyrata has four IRE1 genes, AlIRE1a , ‐b , ‐c and c‐like (Mishiba et al, 2019). Surprisingly, there are three ZmIRE1 genes in maize ( Zea mays B73) – two full‐length genes, which cannot be classified as either IRE1a or ‐b ‐like and a shorter one, which by virtue of its size suggests that it is IRE1c ‐like.…”
Section: Are Two Ire1s Better Than One?mentioning
confidence: 99%
“…IRE1c is largely limited to the Brassicas, is a smaller form that lacks the N‐terminal lumenal or sensory domain and is expressed primarily in flowers (Winter et al, 2007; Figure 4). Reporter constructs involving the IRE1c promoter demonstrated that the gene is expressed in the anther and embryo (Mishiba et al, 2019). The function of IRE1c remained elusive for a long time, because single knockout mutations in IRE1c had no demonstrable phenotype.…”
Section: The Weirdness Of Ire1cmentioning
confidence: 99%
See 2 more Smart Citations
“…While this manuscript was under revision, complementary work on the characterization of IRE1C was published (Mishiba et al, ). The authors indicate that they were not able to isolate an ire1b ire1c homozygous knockout allele using the same combination of parental alleles used in our work.…”
Section: Discussionmentioning
confidence: 99%